A case of cutaneous peripheral T-cell not otherwise specified (PTCL-NOS), successfully treated with brentuximab vedotin after disease progression on standard chemotherapy. (October 2021) - De Francesco, Irene; Wain, Mary; Wong, Denise; Child, Fiona; Dasgupta, Dhruba; Whittaker, Sean; Morris, Stephen Lloyd
Abstract : Cutaneous PTCL-NOS is a rare and aggressive variant of cutaneous T-cell lymphoma with unfavourable prognosis. First line treatment includes anthracycline based regimens. However, the disease tends to be refractory to chemotherapy and patients relapse very quickly. We present a case of cutaneous PTCL-NOS, follicular T-helper phenotype, CD30+, successfully treated with brentuximab vedotin after rapid progression under two standard chemotherapy regimens and TSEBT. The baseline PET/CT in May 2020 (prior to cycle 1 of brentuximab) showed metabolically active subcutaneous nodules throughout the body, with muscle involvement in both legs. The patient already had 2 lines of chemotherapy (CHOP) with progressive multiple focal lesions following cycle 4. The treatment was switched to GCVP – 4 cycles completed 15.08.19 – after which she had further progression. The only available treatment options were either gemcitabine/oxaliplatin containing chemotherapy or CEPP regimen (cyclophosphamide, etoposide, procarbazine, prednisolone). Both treatments had a low chance to be beneficial, considering the rapid progression on the previous two chemotherapy lines. In view of the CD30 positivity (more than 30%) we considered treatment with brentuximab vedotin, which we obtained as compassionate use supply. We started treatment in September 2020 and a restaging PET/CT showed partial response after cycle 4 and complete metabolic response after cycle 8. The patient was still free from recurrence after cycle 13. The treatment tolerance was excellent with only G1–G2 peripheral neuropathy. There was one episode of G3 peripheral neuropathy post cycle 10, which improved back to G1 after giving 2 weeks break from treatment. PTCL NOS is characterised by poor overall survival (20–30% at 5 years) and rapid progression. The treatment with brentuximab vedotin has proven to be safe and effective in our patient, with maintained response at 10 months after treatment initiation.